2020
DOI: 10.1371/journal.pone.0238544
|View full text |Cite
|
Sign up to set email alerts
|

Yoga compared to non-exercise or physical therapy exercise on pain, disability, and quality of life for patients with chronic low back pain: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background Chronic low back pain (CLBP) is a common and often disabling musculoskeletal condition. Yoga has been proven to be an effective therapy for chronic low back pain. However, there are still controversies about the effects of yoga at different follow-up periods and compared with other physical therapy exercises. Objective To critically compare the effects of yoga for patients with chronic low back pain on pain, disability, quality of life with non-exercise (e.g. usual care, education), physical therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 42 publications
(163 reference statements)
2
49
0
1
Order By: Relevance
“…This study also confirmed that yoga may also be an important non-drug intervention to decrease nurse NSCLBP (SUCRA:75.1%), similar to the results of Feilong Zhu et al [52]. There may be two reasons for this.…”
Section: U N C O R R E C T E D P R O O F V E R S I O Nsupporting
confidence: 89%
“…This study also confirmed that yoga may also be an important non-drug intervention to decrease nurse NSCLBP (SUCRA:75.1%), similar to the results of Feilong Zhu et al [52]. There may be two reasons for this.…”
Section: U N C O R R E C T E D P R O O F V E R S I O Nsupporting
confidence: 89%
“…In the case of RMDQ, both the range of improvement (from 0 to 20 points) [42] and the percentage of improvement (30%) were met [37]. Other authors who analyzed interventions in chronic LBP, i.e., yoga [43], obtained a lower SMD value (SMD = −0.30, 95% CI = −0.51 to −0.10, p = 0.003, I 2 = 0%) than that found in the present study with the RMDQ.…”
Section: Discussionmentioning
confidence: 99%
“…However, the improvement in the functional disability status is long-term. Zhu et al also added that Yoga and other exercise or physical therapy had a very similar effect on pain and disability 15 .…”
Section: Discussionmentioning
confidence: 99%